The importance of aerosol mixing state and size-resolved composition on CCN concentration and the variation of the importance with atmospheric aging of aerosols - J. Wang (Atmospheric Chemistry and Physics, 2010)
Aerosol microphysics, chemical composition, and CCN concentrations were measured at the T0 urban supersite in Mexico City during Megacity Initiative: Local and Global Research Observations (MILAGRO) in March 2006. The aerosol size distribution and composition often showed strong diurnal variation associated with traffic emissions and aging of aerosols through coagulation and local photochemical production of secondary aerosol species. CCN concentrations (NCCN) are derived using Köhler theory from the measured aerosol size distribution and various simplified aerosol mixing state and chemical composition, and are compared to concurrent measurements at five supersaturations ranging from 0.11% to 0.35%. The influence of assumed mixing state on calculated NCCN is examined using both aerosols observed during MILAGRO and representative aerosol types. The results indicate that while ambient aerosols often consist of particles with a wide range of compositions at a given size, NCCN may be derived within ~20% assuming an internal mixture (i.e., particles at a given size are mixtures of all participating species, and have the identical composition) if great majority of particles has an overall κ (hygroscopicity parameter) value greater than 0.1. For a non-hygroscopic particle with a diameter of 100 nm, a 3 nm coating of sulfate or nitrate is sufficient to increase its κ from 0 to 0.1. The measurements during MILAGRO suggest that the mixing of non-hygroscopic primary organic aerosol (POA) and black carbon (BC) particles with photochemically produced hygroscopic species and thereby the increase of their κ to 0.1 take place in a few hours during daytime. This rapid process suggests that during daytime, a few tens of kilometers away for POA and BC sources, NCCN may be derived with sufficient accuracy by assuming an internal mixture, and using bulk chemical composition. The rapid mixing also indicates that, at least for very active photochemical environments such as Mexico City, the timescale during daytime for the conversion of hydrophobic POA and BC to hydrophilic particles is substantially shorter than the 1–2 days used in some global models. The conversion time scale is substantially longer during night. Most POA and BC particles emitted during evening hours likely remain non-hygroscopic until efficiently internally mixed with secondary species in the next morning. The results also suggest that the assumed mixing state strongly impacts calculated NCCN only when POA and BC represent a large fraction of the total aerosol volume. One of the implications is that while physically unrealistic, external mixtures, which are used in many global models, may also sufficiently predict NCCN for aged aerosol, as the contribution of non-hygroscopic POA and BC to overall aerosol volume is often substantially reduced due to the condensation of secondary species.